COMPARATIVE ANALYSIS OF ADIPONECTIN AND LEPTIN AS BIOMARKERS OF CHRONIC KIDNEY DISEASE IN INDIVIDUALS WITH EXCESS BODY WEIGHT - Amonov Mukhammad Komil ugli (Modern American Journals, 2025)
Chronic kidney disease (CKD) is increasingly prevalent in the context of rising obesity rates. Adipokines such as adiponectin and leptin play contrasting roles in metabolic regulation and renal pathophysiology. This review compares the diagnostic and prognostic potential of these biomarkers in overweight individuals with CKD. While adiponectin exhibits anti-inflammatory and renoprotective effects, leptin promotes inflammation and fibrosis. Their imbalance—characterized by hypoadiponectinemia and hyperleptinemia—may precede clinical markers of CKD. The leptin/adiponectin ratio may serve as an integrated indicator of metabolic and renal stress, though standardization remains a challenge. Further studies are needed to validate their clinical utility in nephrology.
Keywords: Adiponectin; Leptin; Chronic kidney disease; Obesity; Biomarkers; Adipokines.